1996
DOI: 10.1074/jbc.271.43.26536
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Correction of Bilirubin-UDP-glucuronosyltransferase Deficiency in Gunn Rats by Administration of a Recombinant Adenovirus during the Neonatal Period

Abstract: Injection of a recombinant adenovirus expressing human bilirubin-UGT 1 (Ad-hBUGT 1 ) (3 ؋ 10 9 plaque-forming units (pfu) intravenously) in adult bilirubin-UDPglucuronosyltransferase-1 (BUGT 1 )-deficient Gunn rats resulted in biliary excretion of bilirubin glucuronides and a 70% reduction of serum bilirubin levels. However, the effect was transient, and host humoral and cellular immune response prevented transgene expression after subsequent injections. To determine whether injection during the neonatal perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 18 publications
1
57
1
Order By: Relevance
“…Administration of adenovirus vectors into the trachea, skeletal muscle, thoracic cavity or vasculature of neonatal mice or rats results in transgene expression for several weeks or months. 12,13,[18][19][20][21][22] Subsequent administration of the adenovirus vectors were tolerated and resulted in robust gene expression in some studies 19,20,23 but not others. 18 The relative success of this approach in rodents has been attributed to the relative immaturity of the immune system in the rodent at birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Administration of adenovirus vectors into the trachea, skeletal muscle, thoracic cavity or vasculature of neonatal mice or rats results in transgene expression for several weeks or months. 12,13,[18][19][20][21][22] Subsequent administration of the adenovirus vectors were tolerated and resulted in robust gene expression in some studies 19,20,23 but not others. 18 The relative success of this approach in rodents has been attributed to the relative immaturity of the immune system in the rodent at birth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in neonatal mice and rats have demonstrated that priming with an initial intravenous dose of adenovirus vector resulted in tolerance to subsequent administration of the same vector. 19,23 The intravenous route, which delivers …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include glycogen storage disease type Ia, 1 mucopolysaccharidosis type VII, [2][3][4][5][6] bilirubin-UDP-glucuronosyltransferase deficiency (Crigler-Najjar syndrome), 7,8 haemophilias A 9 and B [10][11][12] and congenital blindness (Leber congenital amaurosis). 13 To fully understand the basis of these successful experiments in order to move towards clinical application, several key factors concerning early gene transfer must be closely examined.…”
Section: Introductionmentioning
confidence: 99%
“…On systemic administration, they localize predominantly to the liver 16,17 and transduce both dividing and nondividing cells. In sufficient doses, these agents can transduce over 90% of all hepatocytes of the liver and so have been used extensively for in vivo hepatic gene transfer.…”
Section: Adenoviral Vectorsmentioning
confidence: 99%